Losy Sakramentarza Tynieckiego podczas II wojny światowej - Sijka, Katarzyna (Saeculum Christianum. Pismo Historyczne, 2019)
The SacramentoriumTynecensis was written in circa 1060-1070, probably in Cologne. It was located in the Benedictine Abbey in Tyniec from 11th century to 19th century. In 1814 the illuminated manuscript was bought by Stanisław Kostka Zamoyski, then in 1818 he located the codex in the Zamoyski Ordynacja Library in Warsaw. It stayed there to the end of World War II. Two formations of Nazi Germany were as follows: a military unit led by Professor of Archaeology, Peter Paulsen and a group led by art historian Kajetan Mühlman. Both were responsible for the plundering of Poland's cultural heritage. They wanted to get the Sacramentorium Tynecensis because it was connected with German culture. The employees of the Zamoyski Ordynacja Library have tried to rescue the codex, sometimes at the risk of their own lives. In 1944 during the action of rescuing library collections from the ruins of the capital city of Poland (action called ‘Pruszkowska’), the manuscript codex was exported and hidden by Stanisław Lorentz in the Cathedral in Łowicz. Thankfully that the ST returned to Warsaw in 1947 and was deposited in the National Library of Poland.